Pengembangan Game Edukasi "Math-Match" Berbantuan Construct 3 Untuk Meningkatkan Kemampuan Numerik Siswa pada Materi Deret Bilangan - Dinardyansyah Fauzurrijal (Fakultas Pendidikan dan Ilmu Pengetahuan, 2026)
This study developed an Android-based educational game titled “Math-Match” as a learning support tool aimed at improving students’ numerical abilities. The development of this educational game employed a Research and Development (RnD) approach using the Thiagarajan 4D model, which consists of four stages: define, design, develop, and disseminate. The research instruments included the educational game developed using Construct 3, a user response questionnaire, Pre-test and Post-test assessments, as well as initial and final numerical ability questionnaires. The goal of this development was to produce an educational game that is valid, effective, and practical. The validity of the game was assessed using a validation questionnaire, which obtained a score of 0.95, categorized as very high. The effectiveness of the game was analyzed using the N-Gain calculation based on Pre-test and Post-test results, yielding a score of 0.61, categorized as moderately effective. The practicality of the game was measured through a user response questionnaire, which achieved a score of 83%, categorized as good. This educational game can still be improved in future research, for example by making it available on platforms other than Android and by adding a leaderboard feature to allow students to compete for the highest scores.
:: Finalisasi Repositori File 3 Juni 2026_Kurnadi
Keywords: Construct 3; Educational Game Development; Students’ Numerical Ability